2017
DOI: 10.1155/2017/7589408
|View full text |Cite
|
Sign up to set email alerts
|

Short- and Long-Term, 11–22 Years, Results after Laparoscopic Nissen Fundoplication in Obese versus Nonobese Patients

Abstract: Background Some studies suggest that obesity is associated with a poor outcome after Laparoscopic Nissen Fundoplication (LNF), whereas others have not replicated these findings. The effect of body mass index (BMI) on the short- and long-term results of LNF is investigated. Methods Inclusion criteria were only patients who undergone a LNF with at least 11-year follow-up data available, patients with preoperative weight and height data available for calculation of BMI (Kg/m2), and patients with a BMI up to a max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 57 publications
(93 reference statements)
2
20
0
Order By: Relevance
“…CT scan in emergency setting may help the surgeon in choosing approach and timing of the procedure. The surgeon with experience of laparoscopic inguinal hernia repair, should consider in patients with stable hemodynamic parameters the operative mini-invasive technique as alternative to conventional laparotomy, in consideration to the advantages in terms of postoperative pain, hospital stay, cosmetic outcomes and laparotomy related morbidity, especially in obese [ 35 ] and young patients.…”
Section: Discussionmentioning
confidence: 99%
“…CT scan in emergency setting may help the surgeon in choosing approach and timing of the procedure. The surgeon with experience of laparoscopic inguinal hernia repair, should consider in patients with stable hemodynamic parameters the operative mini-invasive technique as alternative to conventional laparotomy, in consideration to the advantages in terms of postoperative pain, hospital stay, cosmetic outcomes and laparotomy related morbidity, especially in obese [ 35 ] and young patients.…”
Section: Discussionmentioning
confidence: 99%
“…Improved quality of life, as well as the treatment of obesity and accompanying diseases, has become one of the main goals of obesity surgery treatment. [21][22][23] Research findings have shown that obesity surgery contributes to the improvement of the quality of life of obese patients. [24][25][26][27][28] In our study, it was found that the general health perception of the participants regarding the quality of life was 81.94 out of 100 points.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion there are neither certain data which evidence a correlation between obesity and GCT, nor data to support the hypothesis of a higher incidence of GCT after bariatric surgery. Based on our experience in obese patients [19,20], the finding of neuroendocrine tumors in the pre-operatory phase is not a contraindication for bariatric surgery.…”
Section: Discussionmentioning
confidence: 99%